2018
DOI: 10.1136/bmjopen-2017-021111
|View full text |Cite
|
Sign up to set email alerts
|

Linkage to care among adults being investigated for tuberculosis in South Africa: pilot study of a case manager intervention

Abstract: ObjectivesWe piloted an intervention to determine if support from a case manager would assist adults being investigated for tuberculosis (TB) to link into TB and HIV care.DesignPilot interventional cohort study.Participants and settingPatients identified by primary healthcare clinic staff in South Africa as needing TB investigations were enrolled.InterventionParticipants were supported for 3 months by case managers who facilitated the care pathway by promoting HIV testing, getting laboratory results, calling p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…The low linkage to care rate observed in this study is similar to rates reported in various studies in Southern Africa ( Maraba et al., 2018 ; Bassett et al., 2019 ; Vanqa et al., 2021 ). A multi-centre study conducted in South Africa and Uganda reported a linkage to care rate of 55% (12/22) amongst HIV-positive patients diagnosed with active drug-susceptible TB, while a study in Malawi reported a linkage to care rate of 40% (23/58) amongst hospitalized patients diagnosed with TB in Lilongwe ( Chawla et al., 2016 ; Shapiro et al., 2018 ).…”
Section: Discussionsupporting
confidence: 89%
“…The low linkage to care rate observed in this study is similar to rates reported in various studies in Southern Africa ( Maraba et al., 2018 ; Bassett et al., 2019 ; Vanqa et al., 2021 ). A multi-centre study conducted in South Africa and Uganda reported a linkage to care rate of 55% (12/22) amongst HIV-positive patients diagnosed with active drug-susceptible TB, while a study in Malawi reported a linkage to care rate of 40% (23/58) amongst hospitalized patients diagnosed with TB in Lilongwe ( Chawla et al., 2016 ; Shapiro et al., 2018 ).…”
Section: Discussionsupporting
confidence: 89%
“…Interventions to identify PLHIV receiving care for concomitant TB could facilitate timely entry to the HIV care cascade and ART initiation. In South Africa, a pilot cohort study examined case managers who promoted HIV testing, followed up laboratory results, contacted patients to return for results and facilitated treatment initiation for patients being investigated for TB, resulting in 74% of eligible PLHIV initiating ART [48].…”
Section: Tuberculosismentioning
confidence: 99%
“…In South Africa, studies have implemented elements of patient engagement to reduce patient ILTFU through additional case support managers, various text message reminders and strengthening of ward-based outreach teams. [28][29][30] These patient engagement interventions involve resource-intensive processes focusing on the needs of patients. Our comparatively simple patient interaction process focusing on updating patient contact details, providing practical information and allowing patients the opportunity to ask questions was also aimed at improving the health outcomes of patients.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%